Immunotherapy approaches for managing allergic conditions in children – A narrative review - Agrawal, Amit; Agrawal, Rashmi (Indian Journal of Child Health, 2024)
Allergic reactions in children are a major concern globally. The ever-changing environment, exposure to new and chemically altered compounds, genetically modified food products, variations in hygiene parameters, and most importantly, questionable immunity, together influence the pattern of allergic diseases in children. The most favorable and convenient mode of treatment sought is the use of over-the-counter drugs like antihistamines. However, they tend to lose their efficacy when used over a long period of time. Immunotherapy, for the management of allergic conditions, is considered a gold standard and is still a promising tool. Subcutaneous immunotherapy and sublingual immunotherapy together comprise the two modes of allergen-specific immunotherapy. Each method differs in its mode of administration and role in allergic diseases, in terms of, efficacy and safety measures. The choice between the two is dependent on the type of allergic disease and personal preferences opted either by the specific patient, or by the health-care professional involved in the treatment. The convenience of administration and compliance are also major grounds to consider while opting for the most appropriate mode of treatment. This review hence highlights new advancements in the field of immunotherapy, the efforts to achieve the goals envisioned and literature focusing on better outcomes in managing allergic reactions.